Natural Variation Underlies Differences in ETHYLENE RESPONSE FACTOR17 Activity in Fruit Peel Degreening. Issue 3 (5th February 2018) - Han, Zhenyun; Hu, Yanan; Lv, Yuanda; Rose, Jocelyn K.C.; Sun, Yaqiang; Shen, Fei; Wang, Yi; Zhang, Xinzhong; Xu, Xuefeng; Wu, Ting; Han, Zhenhai
Abstract : ERF17 transcriptional regulation activity in apple fruit peel degreening increases with serine repeat number. Abstract: Through natural or human selection, many fleshy fruits have evolved vivid external or internal coloration, which often develops during ripening. Such developmental changes in color are associated with the biosynthesis of pigments as well as with degreening through chlorophyll degradation. Here, we demonstrated that natural variation in the coding region of the gene ETHYLENE RESPONSE FACTOR17 ( ERF17 ) contributes to apple ( Malus domestica ) fruit peel degreening. Specifically, ERF17 mutant alleles with different serine (Ser) repeat insertions in the coding region exhibited enhanced transcriptional regulation activity in a dual-luciferase reporter assay when more Ser repeats were present. Notably, surface plasmon resonance analysis showed that the number of Ser repeats affected the binding activity of ERF17 to the promoter sequences of chlorophyll degradation-related genes. In addition, overexpression of ERF17 in evergreen apples altered the accumulation of chlorophyll. Furthermore, we demonstrated that ERF17 has been under selection since the origin of apple tree cultivation. Taken together, these results reveal allelic variation underlying an important fruit quality trait and a molecular genetic mechanism associated with apple domestication.